Individual-active form of training of surgeons in their postgraduate education. - V. I. Desiateryk; O. V. Kotov; S. P. Mikhno; O. H. Dunai; V. V. Shapovaliuk (Medičnì Perspektivi, 2018)
Training physicians at the courses not only should increase their general level of education in the specialty, but also provide opportunities for self-improvement through in-depth analysis of their practical activities and introduction of modern techniques and technologies into their own surgical practice. To implement this approach, we have improved the well-known methodology for conducting seminar sessions - the "round table". The main actors in individual seminars were the most experienced doctors. Each of them, if desired, chose the topic of the lesson, which best suited his specialization and work experience. The material was presented in the form of a presentation and consisted of the following main parts: introduction, theoretical and practical parts and conclusions. The most valuable was the practical part, in which the speaker presented his own results of diagnosis and treatment of the pathology that was being considered. Obligatory in this part of the presentation was the section "complications and mortality." The speaker analyzes the new methods of treatment he introduced personally, gives examples from his own practice and demonstrates data of laboratory, radiation, endoscopic diagnostics, photos and video materials. All doctors take part in the discussion. The teacher places the main accents and outlines the ways of further development of science in one or another direction. All 144 listeners who took part in this positively evaluated the innovation. At the same time, 106 (75%) of listeners defined positively the role of the teacher as a moderator of the educational process, and 119 (82,6%) indicated an increase in the motivational component. The fact of obtaining new knowledge and its practical importance was noted by 84 (58,3%) of the listeners. Comparative analysis of the traditional and proposed methods showed the advantage of the latter: 87,4% of positive responses to test assignments based on the proposed method of teaching, versus 71,3% for traditional ones. Thus, the improved “round table” method used has allowed to significantly improve the level of professional training of doctors and to increase the motivational component of lifelong learning.